Chemical characterization of the selenoprotein component of clostridial glycine reductase: identification of selenocysteine as the organoselenium moiety. - Cone, J E (1976)
A small, heat-stable selenoprotein, one of the components of the glycine reductase complex, was labeled with 75Se by growth of Clostridium sticklandii in the presence of Na2 75SeO3. The selenium-containing moiety, which is essential for the biological activity of the protein, was shown to be a selenocysteine residue. It was isolated as its Se-carboxymethyl, Se-carboxyethyl, and Se-aminoethyl derivatives from digests of the pure 75Se-labeled protein that had been reduced and treated with the various alkylating agents prior to hydrolysis. In each instance the 75Se-labeled moiety obtained from an alkylated protein sample and the corresponding alkyl derivative of authentic selenocysteine were indistinguishable. Several studies of the native selenoprotein detected a chromophore (UVmax 238nm) that appeared upon reduction of the protein with KBH4 and rapidly disappeared upon exposure to oxygen. This oxygen-labile chromophore is thought to be the ionized -SeH group of the selenocysteine residue.